Analisis PDRB Perkapita, Investasi Pemerintah, dan Inflasi terhadap Kemandirian Keuangan Daerah Kota Banjarmasin - Reza, Muhammad; Sopiana, Yunita (PPJP ULM, 2023)
The purpose of this study is to determine the analysis of Gross Regional Domestic Product, Government Investment, and Inflation on Regional Financial Independence of Banjarmasin City for the 2010 - 2019 period. The data analysis technique used is multiple linear regression analysis with time series data sourced from BPS Banjarmasin City and the analysis tool uses Eviews10 . The regression equation obtained is Y = -3.561 + 0.349LnX – 0.082LnX2 + 0.787X3 + The results of this study indicate that partially the Gross Regional Domestic Product variable has a significant effect on Regional Financial Independence. While the variables of Government Investment and Inflation have no significant effect on Regional Financial Independence. Simultaneously, Gross Regional Domestic Product, government investment, and inflation have a significant effect on regional financial independence.